A Late Bronze Age/Early Iron Age Hilltop Enclosure with Evidence of Early and Middle Neolithic and Early Medieval Settlement at Carrog, Llanbadrig, Anglesey. (1st December 2014) - Smith, George; Caseldine, Astrid; Griffiths, Catherine; Hopewell, David; Jenkins, David; Lynch, Rances; Madgwick, Richard; Peck, Inga
A small hilltop enclosure at Carrog, Llanbadrig, Anglesey, that had been identified from a crop mark on an aerial photograph was investigated by geophysical survey and subsequently evaluated by excavation. The enclosure was interpreted on typological grounds as a possible Late Bronze Age or Early Iron Age defended site. The enclosure ditch was substantial, but there was no trace remaining of any accompanying bank. Within the enclosure were numerous post-holes and pits. Some of the latter proved to be hearths of Early Neolithic date and these have produced radiocarbon dates in the fourth millennium cal BC. The post-holes appeared to belong to structures from occupation of the enclosure, and dates from these and from the ditch showed that it was probably constructed about 800 cal BC and occupied until about 400 cal BC confirming the original interpretation. Late in its existence the ditch had been partially backfilled and a small building constructed within it, radiocarbon-dated to the eighth–ninth century cal AD.